ANTI-INFLAMMATORY ACTIONS OF BERBERIS LYCIUM (W HOLE PLANT) IN ACUTE AND CHRONIC MODELS OF INFLAMMATION IN MICE - A. M. Minhas; A. U. Khan; G. A. Miana (Journal of Animal and Plant Sciences, 2018)
Berberis lycium Royle (Berberidaceae) is used in the traditional system of medicine for the treatment of rheumatism. The purpose of the current study was to evaluate the anti-inflammatory activity of Berberis lycium, to explore its medicinal use in inflammatory ailments. Berberis lycium crude extract ( Bl.Cr) was investigated in acute (carrageenan and xylene mediated) and chronic (formalin evoked) models of inflammation in mice. Bl.Cr tested positive for alkaloids, carbohydrates, flavonoids, glycosides, phenols, proteins, saponins, steroids and tannins. Bl.Cr caused a dose-dependent (10, 30 and 50 mg/kg i.p) reduction against carrageenan-induce paw edema (P < 0.001 vs. saline group). Bl.Cr (10, 30 and 50 mg/kg i.p) decreases xylene-mediated ear edema (30.64, 54.83 and 72.58 % respectively; P < 0.001 vs. saline group) . In chronic inflammation, Bl.Cr (1 0, 30 and 50 mg/kg i.p) exhibited a dose-dependent reduction in inflammation (P < 0.05, P < 0.01, P < 0.001 vs. saline group). Diclofenac sodium (20 mg/kg), a standard drug also showed similar effects (P < 0.01 vs. saline group). These results indicate that Berberis lycium possesses significant anti-inflammatory activity, thus providing scientific evidence for its folkloric use in the treatment of rheumatism. sodium, rheumatism. 2012) . Traditionally, Berberis lycium is used against
Keywords: Berberis lycium whole plant extract; inflammation models in mice; anti-inflammatory activity; diclofenac